Smart UV Derivative Spectrophotometric Methods for Simultaneous Determination of Metformin and Remogliflozin: Development, Validation and Application to the Formulation - Metformin, Smart UV Derivative Spectrophotometric Methods for Simultaneous Determination of; Development, Remogliflozin; Validation, Validation; Formulation, Application to the (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: The result of pharmaceutical industry research for the new class and the new combination of drugs for the treatments of diabetes is the newly approved combination of metformin (MET) and remogliflozin (REM). For the quality control of this formulation, three smart, reproducible and non-sophisticated spectroscopic techniques were developed by modification of UV spectra. Materials and Methods: The first two methods were based on the measurements of the peak height of the third derivative and second derivative ratio spectra of MET and REM and the third method was the constant center spectrum subtraction method. Results: The proposed methods exhibited Beer’s law in the range of 2.5 to 30 μg/ml and 1 to 24 μg/ml for MET and REM correspondingly by all three methods. The mean percentage recovery was found to be in the range of 99.08% to 100.15% for MET and 98.73% to 100.27% for REM. Further, both analytes were quantified from the formulation using proposed spectroscopic methods with high accuracy. Comparison of all three methods with the reported HPLC method showed no variation in the assay outcomes in relation to accuracy and precision. Conclusion: The suggested techniques are simple, accurate and reproducible, hence could be used for regular quality control of formulation consisting of MET and REM.
Keywords: Metformin; Remogliflozin; UV; Derivative spectroscopy; Validation; Formulation